2008
DOI: 10.1016/j.physd.2008.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of heavy and light particles in turbulence: Comparison between experiments and direct numerical simulations

Abstract: We compare experimental data and numerical simulations for the dynamics of inertial particles with finite density in turbulence. In the experiment, bubbles and solid particles are optically tracked in a turbulent flow of water using an Extended Laser Doppler Velocimetry technique. The probability density functions (PDF) of particle accelerations and their auto-correlation in time are computed. Numerical results are obtained from a direct numerical simulation in which a suspension of passive pointwise particles… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
71
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 28 publications
21
71
6
Order By: Relevance
“…However, measurements in high Reynolds flows showed that particles present highly nonGaussian acceleration probability density function (PDF) [5][6][7][8][9][10][11]. The broad probability tails of high acceleration events are related to the highly non-Gaussian PDF of the velocity increments at small scales.…”
Section: Introductionmentioning
confidence: 99%
“…However, measurements in high Reynolds flows showed that particles present highly nonGaussian acceleration probability density function (PDF) [5][6][7][8][9][10][11]. The broad probability tails of high acceleration events are related to the highly non-Gaussian PDF of the velocity increments at small scales.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in the understanding of the statistical characterization of small particle aggregates have been obtained by studying heavy particles advected by stochastic flows [15][16][17][18], and/or in two-dimensional turbulent flows [19]. Temporal properties along single trajectory have been addressed both numerically and experimentally for small, heavy particles and light particles (see, e.g., [20][21][22][23][24][25][26][27][28]), and for large particles, where inertial effects combine with finite size ones (see e.g. [29][30][31]).…”
Section: Introductionmentioning
confidence: 99%
“…Common examples are represented by small bubbles in liquids, droplets in gases, and aerosols in a generic fluid. The comprehension of the dynamics of these impurities is still an open issue from the theoretical, experimental, and numerical points of view [1][2][3][4][5][6][7][8][9]. Implications are relevant in many applied domains: plankton dynamics in biology [10], chemical reactors, spray combustion and emulsions in industrial engineering [11], planet formation in astrophysics [12], transport of pollutants or floaters, rain initiation and sedimentation processes in geophysics [13].…”
Section: Introductionmentioning
confidence: 99%